Developing, Understanding and Evaluating an Augmented Reality Framework for Universities in Saudi Arabia - Alahmari, Muteeb Saad (Curtin University, 2020)
This research developed and evaluated an Augmented Reality (AR) framework for Universities in Saudi Arabia. A mixed-method design approach was conducted comprising an online survey and interviews to evaluate the framework critically. The research outcomes are a framework with driving factors for effective and efficient implementation and practical recommendations. This research contributes to addressing the lack of empirically validated framework with no or limited data evidence in developing nations especially in Saudi Arabia.